MODULAR FORMS-page87

MODULAR FORMS-page87 - ( x ) 6 = -e x ( f )-1 if f ( x ) =...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
83 Proof. Replacing D with D + div( f ), we do not change the dimensions of the spaces L ( D ) and L ( K X - D ) but change deg( D ) by deg( D + div( f )) = deg D + deg(div( f )). It follows from Riemann-Roch that deg(div( f )) = 0. Corollary 8.2. deg K X = 2 g - 2 . Proof. Take D = 0 and use that L (0) = O ( X ) = C . Here we use that a holomorphic function on compact Riemannian surface is constant. This gives g = dim L ( K X ) . (8.16) Now take D = K X and get deg( K X ) = 2 g - 2. Theorem 8.3. Let b i ( X ) = dim H i ( X, R ) be the Betti numbers of X . Then b 1 = 2 g, b 0 = b 2 = 1 . Proof. Since X is a connected compact manifold of dimension 2, this is equivalent to e ( X ) = 2 X i =0 ( - 1) i b i ( X ) = 2 - 2 g = - deg( K X ) . (8.17) Let f be a non-constant meromorphic function on X (its existence follows from the Riemann-Roch theorem). It defines a holomorphic map f : X P 1 ( C ). For any point x X set e x ( f ) = ( ν x ( f - z ) if f ( x ) = z 6 = - ν x ( f ) if f ( x ) = . (8.18) It is a positive integer. Since deg(div( f - z )) = 0 we obtain X x f - 1 ( z ) e x ( f ) = X x f - 1 ( ) e x ( f ) . (8.19) Notice that, for any x X , ν x ( df ) = ( e x ( f ) - 1 if f
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ( x ) 6 = -e x ( f )-1 if f ( x ) = . (8.20) Here df is the meromorphic dierential dened locally by df dt dt , where t is a local parameter at x . Since the degree of df is nite we obtain that there are only nitely many points x X such that e x ( f ) > 1. In particular, there is a nite subset of points S = { y 1 ,...,y s } in P 1 ( C ) such that, for any y 6 S X x : f ( x )= y e x ( f ) = n = # f-1 ( y ) . (8.21) Taking into account the formulas ( ?? )-(8.21), we obtain 2 g-2 = X x X x (div( df )) = X y : f ( y ) 6 = ( e x ( f )-1) + X y : f ( y )= (-e x ( f )-1) = X x X ( e x ( f )-1)-2 X f ( x )= e x = X x X ( e x ( f )-1)-2 n = X y Y ( n-# f-1 ( y ))-2 n. (8.22)...
View Full Document

Ask a homework question - tutors are online